An experimental study of rotational pressure loss in rotor-stator gap - Yew Chuan Chong; Dave A. Staton; Markus A. Mueller; John Chick (Propulsion and Power Research, 2017)
The annular gap between rotor and stator is an inevitable flow path of a throughflow ventilated electrical machine, but the flow entering the rotor-stator gap is subjected to the effects of rotation. The pressure loss and volumetric flow rate across the rotor-stator gap were measured and compared between rotating and stationary conditions. The experimental measurements found that the flow entering the rotor-stator gap is affected by an additional pressure loss. In the present study, the rotational pressure loss at the entrance of rotor-stator gap is characterised. Based upon dimensional analysis, the coefficient of entrance loss can be correlated with a dimensionless parameter, i.e. rotation ratio. The investigation leads to an original correlation for the entrance loss coefficient of rotor-stator gap arisen from the Coriolis and centrifugal effects in rotating reference frame.